Reciprocal Teaching Berbasis Teknologi dengan Pendekatan Assure di Perguruan Tinggi - Hasan Baharun; Lailatur Rizqiyah (PALAPA, 2019)
This paper presents a model of learning about the use of reciprocal teaching with technology-based approach to ASSURE that will be applied in college. Reciprocal Teaching is becoming one of the learning models that train students to learn independently and active. With the existence of reciprocal learning teaching model of application students are expected to carry out and follow the learning effectively and efficiently. The learning process is basically a direct interaction between the students and educators held aims to to a destination that has meant. In addition the interaction process will bear an effective communication as well as the need for a development that is both instructional media with a melaluli approach to ASSURE. Approach to ASSURE the approach can be a designing a learning through technology-based media. This is necessary in order to set up and customize the process of learning in college by making the liveliness, creativity and independence as well as encourage students to berantusias in studying diligently and follow the lectures. So it is with the application of the reciprocal teaching and pendekatanASSURE in college could create conditions that are more meaningful and enable them to build better personality and character and self-reliance in learning.